A bilayered nanoshell for durable protection of single yeast cells against multiple, simultaneous hostile stimuli. Issue 21 (18th May 2018) - Jiang, Nan; Ying, Guo-Liang; Yetisen, Ali K.; Montelongo, Yunuen; Shen, Ling; Xiao, Yu-Xuan; Busscher, Henk J.; Yang, Xiao-Yu; Su, Bao-Lian
Abstract : A bilayered nanoshell is used to encapsulate a single cell for high stability after hostile stimulation. Abstract : Single cell surface engineering provides the most efficient, non-genetic strategy to enhance cell stability. However, it remains a huge challenge to improve cell stability in complex artificial environments. Here, a soft biohybrid interfacial layer is fabricated on individual living-cell surfaces by their exposure to a suspension of gold nanoparticles andl -cysteine to form a protecting functional layer to which porous silica layers were bound yielding pores with a diameter of 3.9 nm. The living cells within the bilayered nanoshells maintained high viability (96 ± 2%) as demonstrated by agar plating, even after five cycles of simultaneous exposure to high temperature (40 °C), lyticase and UV light. Moreover, yeast cells encapsulated in bilayered nanoshells were more recyclable than native cells due to nutrient storage in the shell.